Augmenting Customer Intention to Use Mypertamina Trough Predictors - Hendra Riofita (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Abstract. This study is conducted regarding the negative responses toward the plan of Indonesian government to apply MyPertamina. Customer intention to use the application is developed. This study employs and measures the capability of buying functions as the predictor of the customer intention to use, as well as customer trust and customer value to mediate the effect of the buying functions on the customer intention to use. The data processed using SPSS and Amos programs is taken using non probable and snowball sampling technique from subsidized fuel customers at the socialization area of MyPertamina. 167 respondents have participated in 10 days online survey to response the 12 statements provided on quostionnaire. The findings show that all hypotheses are supported significantly. Keywords: Trust, value, buying functions, MyPertamina. Abstrak. Penelitian ini dilakukan berkaitan dengan tanggapan negatif terhadap rencana pemerintah Indonesia menerapkan MyPertamina. Customer intention to use dikembangkan. Studi ini menggunakan dan mengukur kemampuan buying functions sebagai prediktor customer intention to use tersebut, dan customer trust dan customer value untuk memediasi pengaruh buying functions terhadap customer intention to use tersebut. Data yang diolah dengan program SPSS dan Amos diambil dengan teknik non probable dan snowball sampling dari pelanggan BBM bersubsidi di area sosialisasi MyPertamina. 167 responden telah berpartisipasi dalam survey online yang diselenggarakan selama 10 hari, untuk menanggapi 12 pernyataan yang disediakan pada kuisioner. Temuan menunjukkan bahwa semua hipotesis didukung secara signifikan. Kata kunci: Trust, value, buying functions, MyPertamina